Comparing the efficacy and safety of second-line therapies for advanced hepatocellular carcinoma: a network meta-analysis of phase III trials. (June 2020) - Wang, Dongxu; Yang, Xu; Lin, Jianzhen; Bai, Yi; Long, Junyu; Yang, Xiaobo; Seery, Samuel; Zhao, Haitao
Background: The prospect for targeted therapies in advanced hepatocellular carcinoma (HCC) has dramatically changed since several recent clinical trials have yielded promising results. The number of second-line therapies is increasing, though the consequent challenge is to consider differences between these interventions. This is a comparative investigation of presently approved second-line drugs for HCC based on findings from phase III randomized controlled trials. Methods: Data related to treatment efficacy including overall survival (OS), progression-free survival (PFS) and objective response rate (ORR) were extracted and compared using a Bayesian approach. Adverse events (AEs) and the rate of discontinuation due to AEs were assessed and compared with provide a more complete understanding. OS and PFS in patients with alpha fetoprotein (AFP) values greater than 400 were compared and ranked as a subgroup. Results: A total of five trials involving 2571 patients were included. The comparison suggests that regorafenib and cabozantinib significantly prolong OS compared with placebo. The rate of AEs and treatment discontinuation did not significantly differ, although the types of AEs varied substantially. Subgroup analysis did not highlight a significant OS difference between regorafenib [hazard ratio (HR) 0.68; 95% confidence interval (CI) 0.50–0.92], cabozantinib (HR 0.71; CI 0.54–0.94) and ramucirumab (HR 0.69; CI 0.57–0.84).Conclusion: Among the four second-line HCC therapies compared, regorafenib and cabozantinib appear to be better choices in terms of OS. Cabozantinib, regorafenib and ramucirumab have similar levels of efficacy for those with AFP >400, although ramucirumab has fewer side effects. No significant difference was observed in AEs, but some AEs related to each of these interventions should be given further consideration.